PEMBERDAYAAN PETANI DI DESA MATTANETE BUA KABUPATEN BONE PROVINSI SULAWESI SELATAN - Muhammad Idris Patarai (Jurnal Pallangga Praja (JPP), 2022)
Empowerment is currently being intensively carried out by the Government. In this article, the authorfocuses on empowering farmers with the aim of developing and optimizing farmers’ skills in managing theiragricultural production. The author uses a qualitative descriptive method with inductive research. Thismethod describes aspects related to the observed and studied focus. The data collection methods used wereobservation, interviews, and document studies. The results showed that the efforts to empower farmers inMattanete Bua Village had been carried out well but there were still some shortcomings such as the regulationscarried out by the Government were not yet fully optimal, the quality of human resources was inadequate,and the participation of the farming community was still very low related to socialization, counseling,agricultural education and training by the Mattanete Bua Village Government. Suggestions from the authorare that the farming community in Mattanete Bua Village should get attention from all related parties, boththe Government and other communities, the empowerment innovations carried out by the Government so thatfarmers can actively participate in the empowerment program implemented, the regulation of agriculturalland and settlements as well as infrastructure that needed by farmers need to be considered.